STUDENTS’ PERCEPTIONS OF TEACHING METHODS USED IN BUSINESS ENGLISH CLASSES IN ECONOMIC UNIVERSITY - Batryn, Natalia Volodymyrivna; Shylinska, Inna Feodosiivna (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2018)
Introduction. Nowadays many teaching methods and strategies are available in higher education offering instructors various alternatives to achieve their teaching goals. A new age of learners requires proactive approaches to integrate innovative teaching into classroom. However, students respond differently to a variety of teaching methods having their personal preferences. Students’ evaluation of teaching strategies is an effective tool that can provide valuable feedback on what they perceive to be more appropriate for them in the process of learning. Purpose. The purpose of this study is to determine students’ perceptions of selected methods used for teaching Business English course in economic university and identify the teaching methods that lead to quality teaching and learning. Methods. Mixed methodology was applied for the study. A total of 250 undergraduates in Ternopil National Economic University, Ukraine completed a questionnaire about the teaching methods used by their instructors in Business English classes representing their perceptions of the most effective ones. 12 instructors of Business English were interviewed during the second stage of the study providing wider responses in regard to what methods they use in the classroom and why they consider the selected methods to be effective in terms of quality teaching. Results. The findings revealed that the interactive methods and problem based learning were identified by students as preferable; however, traditional teacher-centered methods were determined as the most often used. Aligning the teaching strategies with preferences of the students improves learning; however, it is important to consider the educational environment in Ukraine and to align the teaching strategies with both students’ perceptions (based on their preferences and learning styles) and educational environment (including instructors’ workload, student/teacher ratio, number of contact hours per week, etc). Originality. Most research studies investigating the application of innovative interactive teaching methods focus on the advantages of their use. Students’ evaluation of teaching methods and strategies is a valuable feedback on what they perceive to be more effective for them. Besides, instructors’ choice of teaching methods can be directed by several arguments including the conditions that universities provide in Ukraine today. Therefore, the significance of the study and the implications of the potential results are based on effective solving the dilemmas that many instructors face today when integrating innovative teaching methods into the classroom experience. Conclusion. Aligning the teaching strategies with preferences of the students is important. However, in unfavorable environment that does not support the learning process due to several circumstances, it is necessary to investigate what teaching strategies are applied and why the instructors consider the selected teaching methods to be effective under the particular conditions. Then it is critical to find out the ways to implement innovative teaching methods that fit students’ preferences.